Effects of irrigation and nutrients managements with plant intensification on rice under saline soil - Ali, M H; Biswas, P; Islam, M A; Azad, A K (Bangladesh Journal of Nuclear Agriculture, 2024)
The area of salt affected agricultural soils has grown on a global scale. The toxicity of salt and the unfavorable characteristics of the soil are two major causes of the low crop productivity on salt-affected soil. Thus, effective and economical management techniques are required for crop production which may sustainable. The experiments were conducted to identify appropriate irrigation and other management practices for higher yield of Boro rice at two locations (Horinkhola, Satkhira and Batiaghata, Khulna) of saline area during two successive years (2021 and 2022). Six treatments were used, consisting of continuous ponding of irrigation water along with recommended fertilizer (farmers practice, as control), and a range of combination of irrigation water and gypsum fertilizer and foliar spray of Urea, TSP, MOP and Zinc Sulphate. The results revealed that at both locations, the treatments showed significant difference and the highest yield (7.35 t/ha at Horinkhola and 6.75 t/ha Batiaghata) were obtained in treatment T5 [Continuous saturation (0-3cm) + 50% recommended fertilizer except MoP + K2SO4 equivalent to 50% K+ OM + no ridge, high density (15 cm x 10 cm) + Change of standing water 20 days interval + Foliar application of Urea-40 g, TSP-44 g, MOP-26 g and Zinc Sulphate 3g (4 times : 25, 35, 45, 60 DAT)]. Overall, this treatment produced 19% higher yield compared to farmer’s practice, along with maximum BCR (1.57) and net profit (52,004 Tk/ha). This technique can be adopted for higher yield in saline area. Bangladesh J. Nuclear Agric, 38(1): 53-64, 2024